1995
DOI: 10.1021/la00001a032
|View full text |Cite
|
Sign up to set email alerts
|

Surface Diffusion of Sb on Si(111) Measured by Second Harmonic Microscopy

Abstract: Surface diffision of Sb on Si(ll1) has been studied by second harmonic microscopy, which uses surface second harmonic generation to monitor surface concentration profiles with a 3 pm spatial resolution. At temperatures near 55% of the bulk melting point and in the coverage range 0 < 6 < 0.12, the activation energy, &iff, and pre-exponential factor, DO, were found to be 60 f 3 kcdmol and 6 x 103*0.' cm2/s, respectively. The high prefactor and activation energy indicate that the surface diffusion is governed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Also, solutes were often observed to align along specific directions, P was In the case of semiconductors, the very same problems are very likely to affect the data, especially since most APT analysis are performed in laser pulsing mode. Surface migration of various adatoms on Ge [59][60] and Si [61][62] was investigated by several techniques. The difference in the energy barrier for surface migration and desorption was measured to be in the same range (respectively 1.3-2.6 eV and 1.5-3.5 for example for Si [62]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, solutes were often observed to align along specific directions, P was In the case of semiconductors, the very same problems are very likely to affect the data, especially since most APT analysis are performed in laser pulsing mode. Surface migration of various adatoms on Ge [59][60] and Si [61][62] was investigated by several techniques. The difference in the energy barrier for surface migration and desorption was measured to be in the same range (respectively 1.3-2.6 eV and 1.5-3.5 for example for Si [62]).…”
Section: Discussionmentioning
confidence: 99%
“…Surface migration of various adatoms on Ge [59][60] and Si [61][62] was investigated by several techniques. The difference in the energy barrier for surface migration and desorption was measured to be in the same range (respectively 1.3-2.6 eV and 1.5-3.5 for example for Si [62]). This means that such processes are likely to similarly affect the atom probe microanalysis of some semiconductors, when a pole structure is observed within the desorption map [63].…”
Section: Discussionmentioning
confidence: 99%
“…Through use of second-harmonic microscopy ͑SHM͒, we have examined heterodiffusion of group-III and -V adsorbates on group-IV substrates. 9,[12][13][14] The large values for E and D 0 observed for these systems mimic for heterodiffusion the effects just described for self-diffusion. The close correspondence arises from the known ability of the adsorbates to substitute into the top layer of the substrate.…”
Section: Introductionmentioning
confidence: 85%
“…Raw second-harmonic images were processed using methods described previously 13 to remove detector shot noise and broadening from the system's optical response function. The resulting profile was converted to the coverage domain using a calibration curve ͑shown in Sec.…”
Section: A Experimentsmentioning
confidence: 99%
“…The results indicate that the Ga adatom adsorbs stronger on a (110) surface in the case of As or Sb adatom presence with an increased adsorption energy by 0.59 and 0.33 eV, respectively. It is worth noting that although the As enhances the Ga binding more than Sb, it has been reported that the surface diffusion of As is much less than that of Sb, 31,35,36 indicating that Sb has more chance to interact with Ga surface adatoms. Thus, we suggest that the higher radial growth rate with increased Sb 2 flux is due to enhanced (temporary) Ga binding to the Sb adatoms adsorbed on the (110) nanowire side-facet surfaces, which reduces the Ga diffusion on the facets and increases the chance for further radial growth.…”
mentioning
confidence: 99%